2018
DOI: 10.1007/s11883-018-0750-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Ischemic Cardiomyopathy

Abstract: Women with ischemic cardiomyopathy experience significant morbidity and mortality. Differences in underlying pathology, delays in presentation, diagnosis, and treatment as well as the under-representation of women in clinical trials contribute to these poor outcomes. In this review, we discuss the nuances of gender-specific differences in the burden, clinical presentation, and outcomes of ischemic cardiomyopathy in women, in addition to discussion of areas needing further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 136 publications
0
27
0
12
Order By: Relevance
“…Moreover, as gender also influences pathophysiology of cardiomyopathy variable gender was made to a propensity-score matching variable in order to reduce gender-related bias. As Divoky et al 32 and Löchel et al 33 have already presented, the nuances of gender-specific differences are wide-spread in terms of device indication, implantation and postoperative therapy. In our study more women suffered from idiopathic than from ischaemic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, as gender also influences pathophysiology of cardiomyopathy variable gender was made to a propensity-score matching variable in order to reduce gender-related bias. As Divoky et al 32 and Löchel et al 33 have already presented, the nuances of gender-specific differences are wide-spread in terms of device indication, implantation and postoperative therapy. In our study more women suffered from idiopathic than from ischaemic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 98%
“…Sex differences are found in a number of syndromes and diseases in addition to the differences between males and females found in many physiological functions 2729 . For example, menopausal women have more severe manifestations of cardiovascular diseases and hypertension than men due to the physical functions of sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly the investigators performed subgroup analyses and showed a significant interaction for sex, with less benefit in female compared to male patients. Based on the female under-representation in randomized VT ablation trials, their results may not be fully applicable to women [58,59]. As shown in the subgroup analysis of the PAUSE-SCD trial, women may confer no or less benefit from ablation compared to men, though these results should not be over-interpreted as they are based on small sample sizes.…”
Section: Randomized Trialsmentioning
confidence: 99%